Reformasi Pelaksanaan Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Perdagangan Orang - Andriano, Raphael; Adhari, Ade (Syntax Corporation, 2025)
Human Trafficking (TPPO) is an extraordinary crime that threatens human rights, especially children as a vulnerable group. This study analyzes the implementation of legal protection for child victims of TPPO in Indonesia using empirical research methods through in-depth interviews with officials of the Ministry of Women's Empowerment and Child Protection. Data shows a drastic increase in child TPPO cases from 13 cases in 2019 to 794 cases in 2022 in DKI Jakarta. The main findings show that although there has been a comprehensive legal framework through Law No. 21 of 2007 and Law No. 35 of 2014, the implementation of legal protection still faces multidimensional obstacles including low awareness of children as victims, weak family support, difficulties in rehabilitation and social reintegration, and obstacles in the legal evidence process. Improvement efforts made by the Ministry of PPPA include strengthening regulations, establishing a Technical Implementation Unit for the Protection of Women and Children, developing a community-based protection system, and increasing education for law enforcement officers. This study recommends the need to increase the capacity of inter-agency coordination, develop a digital-based integrated monitoring system, and strengthen prevention aspects through economic empowerment programs for vulnerable families..